Enhanced acoustic levitation for non-contact handling system - Foeng, Ardi Firmansyah (2014)
The acoustic levitation pressure profile generated by an acoustic levitator with piezo actuator was studied using force meter equipment that was manufactured to enable measurement of the pressure generated by acoustic levitation in relation to distances from surface. Experiment to test the effect of non-linearity in vibration of piezo actuator to the acoustic pressure generated will also be studied. This project aims to study acoustic levitation pressure profile generated in varying distances and investigate the possibility to enhance the acoustic levitation pressure by manipulating the horns surface which transmits the vibration from the piezo actuator to the vibrating surface. The effect of the manipulation of vibrating profile should alter the acoustic levitation pressure generated. The force meter was manufactured in-house and utilized high precision load cell as a measuring device to quantify the pressure in varying distances. To introduce non-linearity effect to the acoustic levitator, three horns with different surface profile were manufactured and 1mm diameter chrome balls were bought. The horns were then tested on the existing system by replacing the original horn with manufactured horn samples and one sample by having a chrome balls between horn and flexural beam surface. The results of the studies for acoustic levitation pressure profile shows that it conforms to the theoretical hypothesis. The resulting acoustic levitation pressure profile can be represented by a quadratic function when plotted against the gap distance from the surface on the graph, in which shows the inverse quadratic relation to gap distance. The studies of non-linearity introduction in piezo vibration shows a positive result as all the tested horns and chrome balls increase acoustic levitation pressure generated. In conclusion, this project confirms the effect of non-linearity manipulation to the harmonic oscillation of piezo actuator that able to enhance the capability of acoustic levitation in non-contact handling. Further research to study the specific relation of non-linearity in piezo vibration to the acoustic pressure generated could be beneficial to efficiently utilize this method to maximize the acoustic levitation for non-contact handling.